Finding quality in quality improvement: creativity and credibility in higher education - Nevena Martinović; Emma McCallum (Journal of Learning Development in Higher Education)
This opinion piece explores the importance of credibility, reciprocity, and creativity in the quality assurance work of boundary-crossing third space professionals. As educational support professionals (ESPs), we believe that our multiple sources of knowledge and liminal positions are invaluable in guiding quality assurance processes. Our discussion is grounded in Little and Green’s (2022) credibility framework and emphasises the importance of creativity to ensure authentic continuous improvement within a mandatory provincial audit. We suggest that it is imperative, both individually and institutionally, to champion third space professionals in quality assurance roles and ensure they receive the resources they require to meaningfully engage in this work.